2005
DOI: 10.1038/sj.cr.7290376
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of HLA-G expression in a melanoma cell line OCM-1A following the treatment with 5-aza-2′-deoxycytidine

Abstract: The non-classical HLA class I antigen HLA-G is an immune modulator which inhibits the functions of T cells, NK cells, and the Dendritic cells (DC). As a result, HLA-G expression in malignant cells may provide them with a mechanism to escape the immune surveillance. In melanoma, HLA-G antigen expression has been found in 30% of surgically removed lesions but in less than 1% of established cell lines. One possible mechanism underlying the differential HLA-G expression in vivo and in vitro is that the HLA-G gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The mechanism of turning on/off the transcription is not known. Based on the induction of expression of HLA-G using 5-aza2=deoxycytidine it has been suggested that in melanoma cell line methylation of the promoter is one of the major factors [21]. Deacetylation of the histone was also suggested as a possible cause [20].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of turning on/off the transcription is not known. Based on the induction of expression of HLA-G using 5-aza2=deoxycytidine it has been suggested that in melanoma cell line methylation of the promoter is one of the major factors [21]. Deacetylation of the histone was also suggested as a possible cause [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only a few transcription factors and regulatory sequences have been identified until now. Regulation may also act on HLA-G protein expression through the efficiency of translation and the modulation of antigen processing machinery component expression [4,5]. Moreover, in vivo stimulators are likely to be key factors controlling one or several levels of regulation.…”
Section: Introductionmentioning
confidence: 98%
“…5-Aza-2'-deoxycytidine (5-Aza-CdR) is thought to act by inhibiting DNA methyltransferase that methylates cytosine residues in eukaryotic DNA (8). Several researchers have used it as an experimental tool for demethylation (9,10). This drug appears to be incorporated into the cellular DNA where it acts as a non-competitive inhibitor of the maintenance methylase (9,11).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have used it as an experimental tool for demethylation (9,10). This drug appears to be incorporated into the cellular DNA where it acts as a non-competitive inhibitor of the maintenance methylase (9,11). Methyl moieties are thus passively removed when the DNA undergoes replication and, indeed, numerous inactive cellular and viral genes are activated following exposure to 5-Aza-CdR (12).…”
Section: Introductionmentioning
confidence: 99%